Cambodia Economic Update, October 2018 : Recent Economic Developments and Outlook - World Bank Group (World Bank, Phnom Penh, 2018)
Economic growth remains strong, driven primarily by robust expansion in consumption and exports. Domestic demand has been boosted by higher wage growth and larger public investments, with fiscal expansion serving as stimulus. Public outlays were budgeted to increase to 24.6 percent of GDP in 2018 from 23.1 percent in 2017. At the same time, strong external demand has boosted exports of garment and footwear products, which increased 16.1 percent (y/y) during the first half of 2018 - a two year high—from 8.3 percent at the end of 2017. Tourist arrivals reached 3 million during the first six months of 2018, a 13.6 percent increase (y/y), compared with 11.8 percent in 2017, driven by a surge in tourist arrivals by air from China. Capital inflows, mainly comprising foreign direct investment (FDI) continue to increase, underpinning Cambodia's stable external position. Official data showed rising FDI to the manufacturing sector, especially the textile, apparel, and footwear industries, and to agroprocessing. Vibrant construction activity continues to be financed by rising FDI inflows and domestic credit. FDI is estimated to have increased by 14.3 percent (y/y) during the first six months of 2018. About 90 percent of the inflows (excluding those to the financial sector) have originated from China and are directed toward the construction and real estate, agriculture and agroprocessing, and garment sectors. A growing proportion of FDI is now invested in the productive sectors, namely the manufacturing and agriculture sectors, albeit its share remains relatively small at about 20 percent of total inflows.